Decreasing alpha-synuclein aggregation on rotenone-induced adult Zebrafish as Parkinson’s Diseases model by ethanol extraction of Keluwih (Artocarpus camansi) leaves - Marisca Evalina Gondokesumo; Faisal Akhmal Muslikh; Ni Putu Diah Nopitasari; Putu Dea Angelita Putri (Jurnal Teknologi Laboratorium)
The prevalence of Parkinson's disease is increasing every year. This progressive disease is characterized by the loss of neurons in the substantia nigra due to the presence of alpha-synuclein aggregates. Keluwih leaves (Artocarpus camansi) are known to have activity in inhibiting acetylcholinesterase, as well as being an antioxidant and anti-inflammatory. The aim of this study was to evaluate the effect of ethanol extract of A. camansi leaves on the levels of alpha-synuclein in male and female adult zebrafish induced with rotenone. The zebrafish were induced with rotenone at a concentration of 5 µg/L for 28 days, along with the administration of 96% ethanol extract of A. camansi leaves at doses of 2.5, 5, 7.5, or 10 mg/L. The media was changed every 48 hours to maintain the concentration of rotenone and extract. After 28 days, alpha-synuclein levels were examined using immunohistochemistry. The administration of ethanol extract of A. camansi leaves can reduce the average levels of alpha-synuclein in male and female adult zebrafish, with the optimum dose being 2.5 mg/L. Therefore, it can be concluded that the administration of ethanol extract of A. camansi leaves can be used as an alternative treatment for Parkinson's disease.